Enterprise Risk Management and Institutional Performance of Life Insurance Companies in Nepal - Mahat, Nishwarth; Pandey, Surendra; Thapa, Bharat Singh (The Batuk, 2023)
The paper aims at determining the performance of insurance companies in Nepal from the perspectives of enterprise risk management. Risk identification, risk evaluation, risk mitigation, risk implementation and management are predictors of performance of insurance firms. A full fledge structured questionnaire survey was conducted among conveniently selected 100 respondents representing key employees from different branches of insurance firms within the Kathmandu valley. Analysis was made using correlation and step-wise regression. The major finding of the study implies that risk identification, risk assessments and risk mitigation affect positively to insurance firms’ performance whereas, risk management and implementation have negative impact on company’s performance. However, only effect of risk mitigation was found statistically significant. Thus, the insurance companies are suggested to focus on risk mitigation to enhance their performance. Finally, the study also recommends that the firms need to pursue enterprise risk management in line with international best practices to ensure productivity and competitiveness at par with global benchmark.